Putting the social back into sociotechnical: Case studies of co-design in digital health. (12th October 2020) - Papoutsi, Chrysanthi; Wherton, Joseph; Shaw, Sara; Morrison, Clare; Greenhalgh, Trisha
Abstract: Objective: We sought to examine co-design in 3 contrasting case studies of technology-supported change in health care and explain its role in influencing project success. Materials and Methods: Longitudinal case studies of a seizure detection and reporting technology for epilepsy (Southern England, 2018-2019), a telehealth service for heart failure (7 UK sites, 2016-2018), and a remote video consultation service (Scotland-wide, 2019-2020). We carried out interviews with 158 participants and collected more than 200 pages of field notes from observations. Within- and cross-case analysis was informed by sociotechnical theory. Results: In the epilepsy case, co-design prioritized patient-facing features and focused closely around a specific clinic, which led to challenges with sustainability and mainstreaming. In the heart failure case, patient-focused co-design produced an accessible and usable patient portal but resulted in variation in uptake between clinical sites. Successful scale-up of video consultations was explained by a co-design process involving not only the technical interface, but also careful reshaping of work practices. Discussion: A shift is needed from co-designing with technology users to co-designing with patients as service users, and with healthcare staff as professionals . Good co-design needs to involve users, including those who engage with the technology-supported service bothdirectly and indirectly. It requires sensitivity to emergence and unpredictability in complex systems. Healthcare staff need to be supported to accommodate iterative change in the service. Adequate resourcing and infrastructures for systems-focused co-design are essential. Conclusions: If co-design focuses narrowly on the technology, opportunities will be missed to coevolve technologies alongside clinical practices and organizational routines.